RANCANG BANGUN WEBSITE PENJUALAN PAKAIAN MENGGUNAKAN LARAVEL 7 STUDI KASUS RGFOLOSOFI - Andhika Nur Prayoga; Wendy Asswan Cahyadi; Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
This Online Store Design was developed using the Object Oriented Programming approach and the Waterfall method as a system development process model. For the documentation model, this study uses the Unified Modeling Language Tools. While for the implementation of the system using the Laravel 7 Framework and MySQL as a database processor. This website-based Home Industry Rgfolofofi Online Store is expected to facilitate customers and the marketing process for customers and admins.